The application of multiple parallel diodes to control large currents - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This paper discusses a few issues concerning diodes and their application in electric circuits. Considering voltage and current restrictions, experimental and theoretical efforts are made to safely apply semiconducting diodes in circuits working with large current regimes. Combinations of diodes and protecting resistors connected in series and parallel have demonstrated to be of great help with the task of controlling electric currents. To this aim, several activities have enabled participants to observe and measure, or to calculate and display valuable data. Therefore, important class conclusions are stated.